Enhancing Hydrogen Evolution Electrocatalytic Performance in Neutral Media via Nitrogen and Iron Phosphide Interactions. Issue 7 (6th May 2021) - Zhao, Siyu; Xie, Ruikuan; Kang, Liqun; Yang, Manni; He, Xingyu; Li, Wenyao; Wang, Ryan; Brett, Dan J. L.; He, Guanjie; Chai, Guoliang; Parkin, Ivan P.
Abstract : It remains a challenge to develop efficient electrocatalysts in neutral media for hydrogen evolution reaction (HER) due to the sluggish kinetics and switch of the rate determining step. Although metal phosphides are widely used HER catalysts, their structural stability is an issue due to oxidization, and the HER performance in neutral media requires improvement. Herein, a new material, i.e., grapevine‐shaped N‐doped iron phosphide on carbon nanotubes, as an efficient HER catalyst in neutral media is developed. The optimized catalyst shows an overpotential of 256 mV at a large current density of 65 mA cm −2, which is even 10 mV lower than that of the commercial 20% Pt/C catalyst. The excellent performance of the catalyst is further studied by combined computational and experimental techniques, which proves that the interaction between nitrogen and iron phosphides can provide more efficient active structures and stabilize the metal phosphide electrocatalysts for HER. Abstract : N‐doped FeP/carbon nanotube (CNT) grapevine‐shaped catalysts are successfully synthesized by a facile hydrothermal‐annealing method. The introduction of N can enhance the hydrogen evolution performance by optimizing electronic structure and stabilizing the structure of the material simultaneously under working condition. This work provides a facile method to stabilize metal phosphides for electrocatalysis process.